Does Hortense Have a Hoo-Hoo? Gender, Consensus, and the Translation of Gisèle Pineau’s L’espérance-macadam - Stahl, Aletha (TTR, 2000)
AbstractDoes Hortense Have a Hoo-Hoo? Gender, Consensus, and the Translation of Gisèle Pineau's L'espérance-macadam — This article uses an experiment in translating Guadeloupean writer Gisèle Pineau's novel L'espérance-macadam via consensus as a point of departure for analyzing the broader context of translating the French Caribbean for an English-speaking public. Previous efforts at translating recent French Caribbean fiction have focused on the challenge of representing the linguistic spectrum specific to the franco- and creolophone Caribbean. Here, it is suggested that Pineau's particular choices in inflecting French with Creole represent women in important ways, and that an awareness of this gendering of language is germane to translation into English. It is also acknowledged that desires on the part of English-speaking translators are not necessarily innocent but that an awareness of gender and local specificities can contribute to the consensus process entailed in publishing translations and should be part of ongoing debates concerning the French Caribbean in general.